Estrategias de aprendizaje en la optimización del manejo y control de activos fijos en la Cooperativa de Ahorro y Crédito Juventud Unida Ltda. agencia Guaranda, provincia de Bolívar, año 2025. - Rea Rochina, Flor Maritza (2025)
This research aims to propose learning strategies for optimizing the management and control of fixed assets within the Juventud Unida Savings and Credit Cooperative, Guaranda branch, Bolívar Province, during the year 2025. This approach aims to improve the management of fixed assets by implementing a more efficient and efficient management process. For the theoretical framework, two variables were used: learning strategies and fixed asset management, to establish theoretical concepts from different authors as appropriate for the research. It is important to mention that the type of research used is field, descriptive, bibliographic, and applied non-experimental. The research approach is quantitative, and the research methods are deductive and inductive. The population used was all the cooperative's workers. Due to the small population, no sample was used. The techniques used were surveys and systematic observation, and data processing was performed using statistical tables. The project also proposes a comprehensive learning strategy for fixed asset management and control. This program combines structured staff training, the development of a written procedure’s manual governing the acquisition, recording, depreciation, maintenance, and disposal of assets, and systematization using simple technology using advanced spreadsheets and free inventory tools with asset identification.